JAGUAR’S LONG-TERM DATA-DRIVEN MARKETING COMMUNICATION STRATEGY, THE CASE OF THE CZECH REPUBLIC - Kadleček, Jiří (2021)
With rising pressure on lowering CO2 emissions, the automotive industry is moving towards more ecological production methods and striving to be carbon-neutral throughout the lifecycle of the product. Battery Electric Vehicles (BEVs) are gaining more momentum and almost all big automotive players have recently introduced electrified vehicles to their line-up of models. As new products, BEVs are attractive to early adopters who are tech-fans or customers striving to be environmentally friendly. But in order to be profitable, automotive manufacturers need to attract a broad audience and clearly communicate the advantages of full electric vehicles. Countries which offer government subsidies are seeing significant increases in BEV market share.